Visuomotor behaviors and performance in a dual-task paradigm with and without vibrotactile feedback when using a myoelectric controlled hand. Issue 5 (20th October 2018) - Raveh, Eitan; Friedman, Jason; Portnoy, Sigal
ABSTRACT: Prosthesis users allocate visual attention to their prosthetic hand while performing activities of daily living (ADLs), due to absence of sensory feedback. Dual-task assignments present competition for visual attention and may affect the performance of ADLs. Vibrotactile feedback (VTF) is a frequently-used method to provide prosthesis users with tactile feedback. However, the effect of adding VTF on visual attention and performance in a motor dual-task paradigm has not been investigated. Our aim was to compare visual attention and performance during ADLs in a motor dual-task paradigm when using binary VTF and without using VTF. Forty-three able-bodied subjects (age 26 ± 6.6 years) had a myoelectric-controlled hand attached to their right hand. The dual task comprised of a computer game played with the left hand, while manipulating objects with the artificial hand. This was performed with and without VTF in a counter-balanced order of two conditions. An eye-tracker monitored visual attention, while time to complete each task and the time the virtual car went off-road were recorded. No significant differences were found in visual attention or in performance time between the two conditions. Further examination of adding VTF to prosthesis users is recommended, with disrupted visual feedback and basic grasping tasks.